Women In Media Professions In Malaysia: A Study Of Sex Bias In Employment And Work Roles - Kaur, Kiranjit (Pusat Pengajian Ilmu Kemanusiaan, 1982)
This academic exercise hopes to study whether there is any marked Sex bias in the ployment and work roles of women in media professions in Malaysia. It studies sex discrimination in three main areas - namely in employment/recruitment, training, and promotion. A major portion of the paper is on the situation of women at work in the media, in terms of numbers, positions within organisational structures, and problems faced bythe women.